Overall survival in colon cancer patients with different levels of circulating tumor cells and feasibility of enhancing its prognostic value - O. I. Kit; E. Y. Zlatnik; I. A. Novikova; E. P. Ulianova; A. A. Demidova; E. N. Kolesnikov; Yu. A. Gevorkyan; N. V. Soldatkina; A. V. Snezhko (Сибирский онкологический журнал)
Development of personalized approaches to diagnosis, treatment and prognosis of colon cancer (CC) still remains challenging. Levels of circulating tumor (CTC) and cancer stem cells (CSC) are promising non-invasive prognostic factors. Our aim was to assess the overall survival (OS) of patients with stage II–IV CC with different levels of CTCs as well as to enhance their prognostic value by additionally determining the level of CD44+ CSCs. Material and methods. The study included 299 patients with stage II–IV CC. All patients underwent surgery followed by adjuvant chemotherapy (FOLFOX). patients with stage IV CC with resectable liver metastases underwent simultaneous resection of the primary tumor and liver metastases, followed by FOLFOX chemotherapy. the proportion of CTCs was evaluated before surgery using Veridex CellSearch™, and the level of CD44+ CSCs was determined in the tissue of the removed tumor by the IHC method. OS was studied in patients with different CTC levels, cumulative OS was calculated by Kaplan–Meier`s method. prognostic algorithm was designed by logistic regression analysis and cox proportional hazards model. Results. OS was found to be lower in patients with higher CTC levels divided into ranges: 0, 1–3, 4–9, ≥10 (χ2=11.59, p=0.009); thus enabling us to use it for prognosis. its prognostic value is enhanced by estimation of CD44+ CSC in tumor. Statistically significant conjugation between CTC and CD44+ ranges was found. an increase in CTC level by 1 range resulted in the increase in the risk of fatal outcome by 1.58 times (р=0.002); the additive increase in CD44+ expression ≥10 % resulted in the increase in the risk of fatal outcome by 7.2 times (p<0.001). For individual risk assessment, a model for calculating the prognostic coefficient K with high diagnostic sensitivity and specificity was developed, and its mathematical expression was proposed. the value of K≥0.411 indicates a high risk of adverse outcome. Conclusion. The prognostic algorithm for the risk of unfavorable outcome of patients with CC, based on the assessment of CTC and CD44+ CSC levels, was developed.